Montako-kysymystyypin synty ja kehitys - Forsberg, Hannele (Virittäjä, 2006)
Origin and development of the interrogative form montako? How many? (englanti) 3/2006 (110) Origin and development of the interrogative form montako? how many? Finnish has two interrogative constructions for inquiring about an amount or measurable quality: Kuinka/Miten X? How X? and X-ko/-k? X + enclitic question particle. For example, Kuinka/Miten monta? Monta(ko)? How many? and Kuinka/Miten suuri? Suuriko? How big?. The question particle -ko/-k is the same particle used to form yes-no questions. Its appearance in a construction used to form wh-questions is given a new diachronic explanation by the writer. The study follows a discourse-pragmatic approach to grammaticalisation research and is based on comparisons of empirical data on Finnish dialects, spoken and literary Finnish and languages closely related to Finnish. In examining the same subject, Branch (2005) offered an explanation based on the supposition that the meaning of monta has also extended to Kuinka monta? right from the start. The question particle would then have been added later to reinforce the interrogative meaning of monta, and the form Montako? would have been adopted analogically for other words expressing an amount or measurable quality. The writer demonstrates weaknesses in this argument and proposes an alternative explanation. She asserts that the structure is derived from yes-no questions in which a word expressing indefinite quantity is given focus by placing it at the start of the sentence. For example, although Montako sait? is always interpreted in contemporary spoken and written Finnish as a wh-question (How many did you get?), it would originally have been a question asking literally only for confirmation of a state of affairs (Did you get many?). The use of focused yes-no questions in place of wh-questions has been motivated by interactional factors. With these types of question being repeatedly answered in the same way as wh-questions (e.g. Kuinka/Miten monta sait? How many did you get?), i.e. by specifying an amount, the conversational implicatures have become conventionalised and the construction has been gradually grammaticalised in the function of a wh-question (Montako? How many?). Changes have subsequently occurred in the means of focusing questions, and in contemporary Finnish the focus in yes-no questions regarding amounts is often indicated differently, using prosody and the enclitic particle -kin (Saitko montakin? Did you get many?). In southeastern dialects of Finnish and in contemporary spoken Finnish, wh-questions can include forms without the question particle (Monta?, Paljon? How much?and Kauan? How long?), which, the writer contends, can be explained as later changes. In Finnish dialects and in spoken Finnish the use of the Montako? form of interrogative has become limited lexically to three different roots: moni- and paljo-, expressing quantity, and kauka, expressing distance. In literary Finnish this interrogative form has been used analogically with certain other words since the nineteenth century. These are words expressing measurable qualities (e.g. Suuriko? How big?, Pitkk? How long?, Useinko? How often?). In present-day literary Finnish the use of the interrogative form is open for all words belonging to this semantic group. Although the interrogative form Montako? has become grammaticalised in the same function as the long-used construction Kuinka/Miten monta?, it has not displaced it. Instead, both forms survive in parallel, each partially with its own special uses. Hannele Forsberg